2022
DOI: 10.1371/journal.pone.0275801
|View full text |Cite
|
Sign up to set email alerts
|

Implementing quality improvement intervention to improve intrapartum fetal heart rate monitoring during COVID-19 pandemic- observational study

Abstract: Introduction Adherence to intrapartum fetal heart rate monitoring (FHRM) for early decision making in high-risk pregnancies remains a global health challenge. COVID-19 has led to disruption of routine intrapartum care in all income settings. This study aims to evaluate the implementation of quality improvement (QI) intervention to improve intrapartum FHRM and birth outcome before and during pandemic. Method and materials We conducted an observational study among 10,715 pregnant women in a hospital of Nepal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Exclusion of circa 15% of babies born with caesarean section limits the generalisability of the findings. 12 This study was underpowered to explore differences in outcome beyond admission to neonatal intensive care unit. Lastly, the potential relationship between non-crying and hypoxia as the explanatory mechanism for bradycardia and tachycardia could not be defined due to lack of concomitant oxygen saturation measurement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Exclusion of circa 15% of babies born with caesarean section limits the generalisability of the findings. 12 This study was underpowered to explore differences in outcome beyond admission to neonatal intensive care unit. Lastly, the potential relationship between non-crying and hypoxia as the explanatory mechanism for bradycardia and tachycardia could not be defined due to lack of concomitant oxygen saturation measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome data of the study were measured with NeoBeat HR monitor that has been shown to record efficient and reliable HR data 13. Trained external data collectors directly observed all births and classified crying status immediately after stabilisation 11 12 21. To further increase reliability of the crying classification, we cross-tabulated data from breathing observations made real time during the initial stabilisation and found high rates of agreement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations